ANALYSIS OF THE QUALITY COMPONENTS OF RIGID ROAD PAVEMENTS IN RELATION TO VEHICLE VOLUME USING THE PD T-14-2003 METHOD AND THE SNI 8457 2017 METHOD - Revaldi, M. Alvin; Prabowo, Yudi Setio (Departement of Civil Engineering, Universitas Winaya Mukti, 2025)
Highways are vital infrastructure in supporting land transportation systems, community mobility, and logistics distribution. To ensure safety, comfort, and structural durability, highway pavement design must be based on appropriate technical standards. This study aims to analyze the quality components of rigid highway pavement based on vehicle volume using two methods: Pd T-14-2003 and SNI 8457:2017, with a case study on the pavement project of the Cimanying–Jipu highway section. Primary data was obtained through field observations, while secondary data was obtained from relevant agencies, including traffic volume, vehicle types, and projections of average daily traffic growth. Based on a subgrade CBR value of 26%, both methods resulted in a concrete layer thickness of 20 cm, with concrete quality K-175 (Pd T-14-2003) and K-225 (SNI 8457:2017). Detailed calculations show differences in reinforcement specifications between the two methods. The analysis results indicate that SNI 8457:2017 specifies smaller dowel dimensions but with closer installation spacing, while Pd T-14-2003 requires larger reinforcement dimensions. This study helps provide recommendations for selecting a more economical and effective rigid pavement design method based on traffic conditions and site characteristics.